2014
DOI: 10.1016/j.biocel.2014.06.015
|View full text |Cite
|
Sign up to set email alerts
|

LL-37 attenuates inflammatory impairment via mTOR signaling-dependent mitochondrial protection

Abstract: a b s t r a c tThe human cationic antimicrobial protein LL-37 is a multifunctional host defense peptide with a wide range of immunomodulatory activities. Previous work has shown that LL-37 exerts both pro-and antiinflammatory effects. The role of mitochondria in the skin inflammatory effects of LL-37 has not been well studied. Therefore, our aim was to investigate the immunomodulatory effect of LL-37 in HaCaT cells and to delineate the underlying mechanisms related to mitochondrial function. Immunohistochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
(40 reference statements)
1
5
0
1
Order By: Relevance
“…It is hypothesized that mitochondria may provide a robust indicator of bioenergetic crisis because they are sensitive to redox status (Bonnard et al, 2008), acute and chronic inflammation (Sun et al, 2014; Quoilin et al, 2014; Zapelini et al, 2008), and metabolic stress (Russell et al, 2002; Widlansky et al, 2010; Schulz et al, 2007), which are common features among many of the complex, chronic diseases associated with aging (Chacko et al, 2014; Kramer et al, 2014). Peripheral blood cells may recapitulate bioenergetic signatures found in skeletal muscle and other vascular tissues.…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that mitochondria may provide a robust indicator of bioenergetic crisis because they are sensitive to redox status (Bonnard et al, 2008), acute and chronic inflammation (Sun et al, 2014; Quoilin et al, 2014; Zapelini et al, 2008), and metabolic stress (Russell et al, 2002; Widlansky et al, 2010; Schulz et al, 2007), which are common features among many of the complex, chronic diseases associated with aging (Chacko et al, 2014; Kramer et al, 2014). Peripheral blood cells may recapitulate bioenergetic signatures found in skeletal muscle and other vascular tissues.…”
Section: Discussionmentioning
confidence: 99%
“…IL-32-induced pro-inflammatory cytokines such as TNF-α, IL-1β, and IL-6 were inhibited by LL-37 through activation of the phosphorylation of MKP-1 (S359), a negative regulator of inflammation. Moreover, LL-37 can also attenuate inflammatory impairment through stimulating mitochondrial biogenesis and protecting mitochondrial function, which are dependent on mTOR signaling …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a previous study showed that inflammatory conditions or arginine catabolism could affect mitochondrial function (Lee and Huttemann, 2014;Tang et al, 2020). Sun et al indicated that the antiinflammatory effects of CAMP were dependent its ability to stimulate mitochondrial biogenesis and maintain mitochondrial homeostasis (Sun et al, 2014). Tang et al (2020) also found that the loss of ARG1 could cause arginine accumulation and mitochondrial dynamics disruption.…”
Section: Discussionmentioning
confidence: 99%